Academic Mobility and Immigration Trends in South African Higher Education Institutions - Maharaj, Ashika (Journal of Economics and Behavioral Studies, 2016)
This paper seeks to offer an insighton the subject of academic mobility into South African Higher Education Institutions (HEI’s). This is done by examining the current academic landscape in South Africavia a comparisonbetween the profile of South African (SA) academics andexpatriate academics. Currently, SA is facing major skills and staffing shortages locally in terms of Science, Engineering and Agriculture. The Departmentof Higher Education and Training as well as SA universities have advocated to run programmes in scarce skills disciplines through the recruitment of expatriate academics. The research reported in this paper adopted a non-experimental research design of ex post facto type, using a correlational approach. The data used are the statistical records of all academics in South African higher education for the 2005/2010/2014 academic years as provided by the Higher Education Management Information Systems (HEMIS) of SA. Descriptive statistics as well as inferential statistics were also used to analyze the data. The results revealed that there were no significant differences in age between SA and expatriate academics nationally over the three years. A comparison of the academic qualifications of SA and expatriate academics over the three years indicates that expatriate academics are more highly qualified than their SA colleagues, as the majority of the former hold a doctoral degree. The majority of expatriate academics are recruited from SADC countries as well as other African countries. Interestingly enough, the next most frequent major supply region of expatriate academics to South Africa is Europe. WITS and UCT were consistently ranked first and second in terms of the number of expatriate academics employed over the three years. Both are among the leading five higher education institutions in South Africa in terms of their research outputs as well as the number of PhDs per member of staff.